How do emoticons affect youth social interaction? The impact of emoticon use on youths online interpersonal interactions - Ju, Gaofei; Zhao, Ru (Frontiers in Communication, 2024)
Emoticons are non-verbal symbols that are employed during online interactions, and they constitute an integral component of online interpersonal communication. The influence of emoticons on the online interpersonal interactions of young people was investigated through in-depth interviews with 25 young people who utilize emoticons to a moderate or significant extent. The study identified three key aspects through which the impact of emoticons on youth’s online social interactions is manifested. Firstly, this is reflected in the level of emotion and meaning conveyed. The utilization of emoticons by young people has, to a certain extent, rectified the contextual limitation of “embodied absence” in online virtual social interaction. Secondly, this is reflected in young people’s recognition of emoticons. The use of emoticons by young people in online social interactions has led to the formation of a distinct “emoticon community.” This phenomenon not only facilitates the development of a more profound social identity among young people in online social interactions but also contributes to the expansion of the adolescent network, resulting in the emergence of a novel “social divide.” Thirdly, the use of emoticons by young people can be seen to contribute to a sense of alienation. As young people become increasingly reliant on emoticons, their influence is gradually extending from the digital realm to the physical world, impacting the normal social interactions of young people in real life. Emoticons have gradually become a means of facilitating young people’s online socialization, but they have also had the unintended consequence of limiting their normal social interaction. The deterioration of online interpersonal communication among young people is a key factor in the symbolic generalization and alienation of expression in the use of emoticons by this demographic.